Notebook [37, Spring 1996] - Leier, Mark (James Mark) (Labour/Le Travail, 1996)
Opens with a "labour quote" drawn from Jack London's "War of the Classes" (1905) and promises that this will be a "new and irregular" feature. Reports on varioius forthcoming conferences with labour/work themes.